2015
DOI: 10.1016/j.nbd.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Hematogenous macrophage depletion reduces the fibrotic scar and increases axonal growth after spinal cord injury

Abstract: Spinal cord injury (SCI) leads to formation of a fibrotic scar that is inhibitory to axon regeneration. Recent evidence indicates that the fibrotic scar is formed by perivascular fibroblasts, but the mechanism by which they are recruited to the injury site is unknown. Using bone marrow transplantation in mouse model of spinal cord injury, we show that fibroblasts in the fibrotic scar are associated with hematogenous macrophages rather than microglia, which are limited to the surrounding astroglial scar. Deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
180
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(194 citation statements)
references
References 44 publications
13
180
0
1
Order By: Relevance
“…The rapid influx of immune cells into an injured spinal cord contributes to a cascade of secondary injury processes that lead to further axonal damage, cell death, demyelination and fibrosis and reactive gliosis with scar formation (Popovich et al, 1999; Fleming et al, 2006; Donnelly and Popovich, 2008; Evans et al, 2014; Zhu et al, 2015a). Systemic depression of monocytes and/or macrophages through administration of liposome-encapsulated clodronate (Popovich et al, 1999; Zhu et al, 2015a), dehydroepiandrosterone (Fiore et al, 2004), minocycline (Stirling et al, 2004), FK506 (Lopez-Vales et al, 2005), or antibody to alphaD (Mabon et al, 2000) improves tissue repair and enhances functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid influx of immune cells into an injured spinal cord contributes to a cascade of secondary injury processes that lead to further axonal damage, cell death, demyelination and fibrosis and reactive gliosis with scar formation (Popovich et al, 1999; Fleming et al, 2006; Donnelly and Popovich, 2008; Evans et al, 2014; Zhu et al, 2015a). Systemic depression of monocytes and/or macrophages through administration of liposome-encapsulated clodronate (Popovich et al, 1999; Zhu et al, 2015a), dehydroepiandrosterone (Fiore et al, 2004), minocycline (Stirling et al, 2004), FK506 (Lopez-Vales et al, 2005), or antibody to alphaD (Mabon et al, 2000) improves tissue repair and enhances functional recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…SCI leads to scarring at the lesion site that includes both fibrotic and gliotic responses (Goritz et al, 2011; Soderblom et al, 2013; Zhu et al, 2015a; Zhu et al, 2015b). The lesional scar inhibits axonal regeneration through a number of mechanisms including accumulation of molecules that are inhibitory to axonal outgrowth, such as chondroitin sulfate proteoglycans (CSPGs), and acting as a physical impediment to axon elongation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin debris and CSPGs, both inhibitory to axon regeneration, accumulate in the lesion core and the glial scar. Hematogenous macrophages start to infiltrate the lesion (30, 31) and attract perivascular fibroblasts that separate from blood vessels and form the fibrotic scar (32, 33) peaking in density by 7 days after SCI. By 14 days after SCI, the scar has started to mature and form tight borders between the glial and fibrotic components of the scar (20, 21, 33) (Figure 1E).…”
Section: Scar Formation After Contusive Scimentioning
confidence: 99%
“…By intrathecal bone marrow cells transplantation, Zhu et al 40 demonstrated that gliosos is more associated with macrophages than microglia in mice. Depletion of these macrophages resulted in a reduction of fibroblasts and the formation of basal lamina, leading to a scar less fibrotic and more conducive to axonal growth.…”
Section: Glial Scarmentioning
confidence: 99%